(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article deals with the features of rehabilitation of stutterers, directions of rehabilitation work development in stutterers rhythmized speech with the help of various psychological, psychotherapeutic and corrective pedagogical influences.